(Ø§Ù„Ø¹Ø§Ø¯Ø©ÙŠÙˆÙˆØ§Ù†Ø¬Ø¹Ø§Ù†ØªÙŠÙ†ÙÙŠÙ†Ø¸Ø±Ø§Ù„Ø£ØÙƒØ§Ù…Ø§Ù„Ø´Ø±ÙŠØ¹Ø©Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© (Ø¯Ø±Ø§Ø³Ø©Ù…ÙŠØ¯Ø§Ù†ÙŠØ© :ØÙˆÙ„Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ÙƒØ§Ø¬ÙŠØ¬Ø§Ù†Ø¬Ø¥Ø³Ù„Ø§Ù…Ø¨ÙˆØ¹Ø§ÙŠØ©ÙƒØ§Ø¹ÙŠÙ†Ø¨Ø§Ø¨Ø§Ù†Ø¯Ø§Ù…ÙƒØ§Ø±Ø§Ù†Ø¬Ø§Ø³Ø§Ù…Ø¨Ø§Ù„ÙŠ - Khalid, Idham; Anshori, Isa; Masduqi, Ahmad (Maqasid: Jurnal Studi Hukum Islam, 2020)
ABSTRACTIn the Balinese community, especially the people in the Kecicang Islam Village of Bungaya Village Kangin Bebandem Karangasem, there is a tradition in the marriage process called "Nyuang Nganten". This tradition one day before the contract of the prospective bridegroom brings the prospective bride to his residence at night. In this tradition, the bride and groom are picked up by the bridegroom's relatives and accompanied by the community while in this tradition the bridegroom's family brings something like betel leaves, sugar, prestige, coffee, tobacco and others.From the background of the problem, the writer formulates the problem into 2 questions, namely 1) How is the Nyuang Nganten tradition in the Islamic village of Kecicang? 2) What are the views of scholars and community leaders about the Nyuang Nganten tradition ?. This research is a field research using qualitative-descriptive method. The method used for data collection is by observation, interview, and documentation.The conclusion of this research is that the Nyuang Nganten tradition of the Kecicang Islam village of Bungaya Kangin Village is a hereditary heritage of ancestors so that it still exists. This custom is a prerequisite before holding a marriage in Kampung Kecicang Islam.Â  In the procession before the wedding there are several meetings required to bring up to smoothen the marriage. According to as community and religious leaders, the Nyuang Nganten custom is a necessity in marriage in the Kampung Kecicang Islam community and even if this custom is not implemented, we are not considered as respecting the custom and violate local regulations and this affects the psychological family. The views of scholars and community leaders in Kampung Kecicang Islam believe that the Nyuang Nganten custom does not violate Islamic law. In fact, this tradition may be worked on and/or abandoned.Keywords: Tradition, Nyuang Nganten, Islamic Law